Structure and biological activity of human homologs of the raf/mil oncogene. - Bonner, T I (1985)
Two human genes homologous to the raf/mil oncogene have been cloned and sequenced. One, c-raf-2, is a processed pseudogene; the other, c-raf-1, contains nine exons homologous to both raf and mil and two additional exons homologous to mil. A 3' portion of c-raf-1 containing six of the seven amino acid differences relative to murine v-raf can substitute for the 3' portion of v-raf in a transformation assay. Sequence homologies between c-raf-1 and Moloney leukemia virus at both ends of v-raf indicate that the viral gene was acquired by homologous recombination. Although the data are consistent with the traditional model of retroviral transduction, they also raise the possibility that the transduction occurred in a double crossover event between proviral DNA and the murine gene.